2018
DOI: 10.3389/fpsyg.2018.02356
|View full text |Cite
|
Sign up to set email alerts
|

The Role of School Adaptation and Self-Concept in Influencing Chinese High School Students’ Growth in Math Achievement

Abstract: A longitudinal designed research study was conducted to provide empirical evidence regarding the influences of three dimensions of students’ school adaptation on their math achievement growth over the first year of high school. These dimensions included learning adaptation, stress management, and personal communication. Student math achievement growth was measured using the student growth percentile (SGP) score. Structural equation modeling (SEM) was used to test for the possible mediating role of self-concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 68 publications
1
14
0
Order By: Relevance
“…After one year or multiple years, they passed the examination and then re‐entered senior high school at an older age. First‐year students have just experienced the pressure of entering a higher‐level school, thus showing their ability to resist stress and undergo an intense psychological experience (Zhang et al, 2018). They are able to recognize and evaluate themselves more accurately and provide a better representation of adolescent groups overall.…”
Section: Discussionmentioning
confidence: 99%
“…After one year or multiple years, they passed the examination and then re‐entered senior high school at an older age. First‐year students have just experienced the pressure of entering a higher‐level school, thus showing their ability to resist stress and undergo an intense psychological experience (Zhang et al, 2018). They are able to recognize and evaluate themselves more accurately and provide a better representation of adolescent groups overall.…”
Section: Discussionmentioning
confidence: 99%
“…A number of scientists point to gender differences in adaptation process: they all agree that the adaptation process is harder for girls since they are more prone to stresses and depressed mood, which ties https://doi. org/10.15405/epsbs.2019.09.02.41 Corresponding Author: Aleksei N. Bogachev Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 2357-1330 357 with their need for approval, search for external social support and lack of independence (Clinciu, 2013;Mudhovozi, 2012;Zhang, Cui, Zhou, Cai, & Liu, 2018).…”
Section: South-african Scientistsmentioning
confidence: 99%
“…According to Marsh and Martin (2011, p. 60), student academic self-concept refers to "students' personal beliefs of their academic abilities and skills that are developed through experience with and interpreting the learning environment. " It is suggested that how individual students conceive themselves and their abilities can largely affect their academic motivation (Emmanuel et al, 2014;Seaton et al, 2014), academic growth (Zhang et al, 2018), academic achievement (McInerney et al, 2012Chao et al, 2019), and success (Prince and Nurius, 2014;Lohbeck et al, 2017). Accordingly, determining factors that may positively affect students' academic self-concept seems essential.…”
Section: Introductionmentioning
confidence: 99%